The effects of causal and self-efficacy beliefs on help-seeking for people with depressive complaints: a quasi-experimental online study - McLaren, Thomas; Peter, Lina-Jolien; Tomczyk, Samuel; Muehlan, Holger; Schomerus, Georg; Schmidt, Silke (Frontiers in Psychiatry, 2023)
Background. Only about a third of people with depressive symptoms seek professional health care. Furthermore, people labelled as mentally ill may experience stigmatisation, which can impede help-seeking behaviour. Aim. To examine the effects of three vignette-based interventions endorsing biopsychosocial causal beliefs and strengthening self-efficacy on help-seeking intention and behaviour as well as the predictive values of these variables and previous treatment experience. Method. A quasi-experimental online study utilising a fractioned factorial design was carried out. People were screened for depressive symptoms and their current treatment status. After baseline assessment they were randomly allocated into one of 24 groups receiving a combination of interventional messages. Actual help-seeking behaviour was measured at follow-ups three and six months after baseline. Results. Altogether, N=1368 participants are included in the final analyses and N=983 provided data on their help-seeking behaviour within three to six months after the baseline assessment. The intention to seek help from a general practitioner or a mental health professional is significantly influenced by the interventions. However, help-seeking behaviour is not influenced by the interventions. On a conceptual level, biopsychosocial causal beliefs (β=.09 – .23) and self-efficacy to seek help (β=.16 – .25) predict help-seeking intention. There is a negative interaction effect of both self-efficacy beliefs on intention and behaviour which changes depending on depression severity. In all models, intention is the main predictor of actual behaviour. Treatment experience predicted both help-seeking intention and behaviour. Conclusion. Biopsychosocial causal beliefs as well as self-efficacy have a direct effect on help-seeking intention. Interventions should include information on how to actually seek help as a means to strengthen self-efficacy beliefs and simulate previous treatment experience. Further research is needed to investigate the respective interaction effects on intention and behaviour.